Regulatory effects of oral microbe on intestinal microbiota and the illness - Lu, Yanbei; Li, Zhengyi; Peng, Xian (Frontiers in Cellular and Infection Microbiology, 2023)
Over the past decade, the association between oral health, intestinal microbiota, and systemic diseases has been further validated. Some oral microbial species have been isolated from pathological intestine mucosa or feces and identified as biomarkers for intestinal diseases. A small proportion of oral microbiome passes through or colonizes the lower gastrointestinal tract, even in healthy individuals. Opportunistic pathogens from the oral cavity may expand and participate in the occurrence and progression of intestinal diseases when the anatomical barrier is disrupted. These disruptors interact with the intestinal microbiota, disturbing indigenous microorganisms, and mucosal barriers through direct colonization, blood circulation, or derived metabolite pathways. While interacting with the host’s immune system, oral-derived pathogens stimulate inflammation responses and guide the transition of the intestinal microenvironment from a healthy state to a pre-disease state. Therefore, the oral-gut microbiome axis sheds light on new clinical therapy options, and gastrointestinal tract ecology balance necessitates simultaneous consideration of both oral and gut microbiomes. This review summarizes possible routes of oral microbes entering the intestine and the effects of certain oral bacteria on intestinal microbiota and the host’s immune responses.